Culturally relevant school leadership for Syrian refugee students in challenging circumstances. (November 2019) - Arar, Khalid; Örücü, Deniz; Ak Küçükçayır, Gülnur
This article presents two rich case studies of schools catering for Syrian refugee students in the Turkish city of Ankara. The article attempts to identify the challenges facing the two schools in this complex reality and the strategies developed by the two principals and their teaching staff to cope with academic, pedagogic and administrative functioning difficulties. Qualitative data collection and analysis were chosen for this investigation. Interpretation followed the four dimensions suggested by Horsford, Grosland and Gunn (2011) in their Framework for Culturally Relevant Leadership: political contexts, pedagogical approaches, personal journeys and professional duties. Findings indicate that although the schools cope with difficult circumstances in the field, the government's policies are naive and unclear. The principals are motivated by a pedagogy of compassion, containment and humanistic-universal commitment. Conflicting discourses are found among the staff who feel 'trapped' in this difficult reality. The principals employ a style that encourages synergistic collective commitment and social cohesion. Conclusions and recommendations are discussed.